Implementasi Program Gerakan Literasi Sekolah Menggunakan Teknik Membaca Ideovisual di Sekolah Luar Biasa YPAC Banda Aceh - Ardhian, Safura Maula; Safri, T. Mulkan; Nurrahmi, Nurrahmi; Yuliana, Cut Putroe (Baitul 'Ulum: Jurnal Ilmu Perpustakaan dan Informasi, 2024)
The ideovisual reading technique is the "Implementation of the Ideovisual Reading Technique to Support the School Literacy Movement in Special Schools for the Deaf (SLB-B) under the YPAC Foundation for Child Development (YPAC) Banda Aceh." The aim is to understand the implementation of ideovisual reading for deaf students in SLB-B YPAC Banda Aceh and identify the challenges faced in applying ideovisual reading at SLB-B YPAC Banda Aceh. The subjects of this study are three high school teachers from SLB-B YPAC Banda Aceh. This research employs a qualitative descriptive approach. Data collection techniques include observation, interviews, and documentation. The results of the study show that ideovisual reading is implemented in teaching deaf students at SLB-B YPAC Banda Aceh through the stages of the School Literacy Movement (GLS), which consist of planning, implementation, and evaluation stages. In the planning stage, adjustments are made to materials according to students' needs and the planning of school literacy movement activities. The implementation stage involves applying ideovisual reading, teacher-student interactions, and student participation in the school literacy movement. In the evaluation stage, assessments are conducted on the consistency of using visual media in learning, the intensity of literacy application, the variety of reading materials, the frequency of book borrowing, and the presentation of information to students. Ideovisual reading has become a technique used by teachers to deliver materials, thus enhancing the literacy skills of deaf students. However, its application at SLB-B YPAC Banda Aceh faces minor challenges, including a lack of supporting tools, limited teacher skills in using ideovisual media, and differences in learning curricula. The solutions to these challenges include providing the necessary equipment by the school and training teachers in ideovisual reading skills. Thus, the implementation of ideovisual reading media can be further developed to support the literacy development of deaf students at SLB-B YPAC Banda Aceh. Keywords: Ideovisual Reading, School Literacy Movement